ANALISIS ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) DENGAN TIME SERIES APPROACH DALAM PENILAIAN KINERJA KEUANGAN PERUSAHAAN SELAMA PANDEMI (Studi pada Industri Pertanian di Indonesia Yang Listing di BEI) - Latisha Ananda Rezha; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2021)
The purpose of this study was to determine the financial performance of the Industrial Agriculture Sector in Indonesia which was listed on the Indonesia Stock Exchange for the 2020’s pandemic period with the Economic Value Added (EVA) and Market Value Added (MVA) approaches with the Time Series Approach. The results of this study were based on the Economic Value Added (EVA ) shows that PT. Andira Agro Tbk, PT. Eagle High Plantations Tbk, PT. Jaya Agra Wattie Tbk, PT. Dharma Samudera Fishing Industries Tbk, PT. Estika Tata Tiara Tbk and PT. BISI International Tbk. negative results are said to perform poorly. PT. Dharma Satya Nusantara Tbk. Positive results is said to perform well. Based on Market Value Added (MVA) of PT. Dharma Samudera Fishing Industries Tbk. negative results is said to perform poorly. PT. Andira Agro Tbk, PT. Eagle High Plantations Tbk, PT. Dharma Satya Nusantara Tbk, PT. Jaya Agra Wattie Tbk, PT. Estika Tata Tiara Tbk and PT. BISI International Tbk positive are said to perform well. Economic Value Added (EVA) and Market Value Added (MVA) assessments in the Industrial Agriculture Sector in Indonesia of 1,006,193.77 indicate a positive result. This shows that the Industrial Agriculture Sector in Indonesia as a whole is said to good perform. Keywords: Economic Value Added (EVA) dan Market Value Added (MVA) Kinerja Perusahaan Sektor Industri Pertanian, Pandemi